PENGARUH FEE AUDIT, AUDIT TENURE, ROTASI AUDIT DAN REPUTASI AUDITOR TERHADAP KUALITAS AUDIT AUDIT (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI tahun 2017-2019) - Eriesta Mauliana; Herry Laksito (Diponegoro Journal of Accounting, 2021)
The development of manufacturing companies in Indonesia will increase the demand for quality audit reports produced from independent third parties or auditors. This study has a purpose to examine the effect of audit fees, audit tenure, audit rotation, and auditor reputation on audit quality. The independent research variables that used in this study are audit fees, audit tenure, audit rotation and auditor reputation. While the dependent variable that used in this study is audit quality. The population in this study consists all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The research sample was taken by using purposive sampling method. Based on the criteria, data sample of 49 manufacturing companies with 3 (three) years of observation. So the final amounts of the sample are 147. The research was analyzed by using logistic regression analysis with the application of the SPSS 26 program. The results of this study indicate that audit fees have a positive effect on audit quality, audit tenure has a negative effect on audit quality, audit rotation has a positive effect on audit quality and auditor reputation has no effect on audit quality.